RAW ROCK PHOSPHATE AS SUBSTITUTE FOR BONE MEAL IN DIETS OF BROILER CHICKENS - IKANI, E. I.; ADUKU, A.O.; BALOGUN, T.F.; OGUNDIPE, S.O. (Nigerian Journal of Animal Science, 2023)
An experiment was conducted to determine the optimum replacement value of Raw Rock Phosphate (RRP) for bone meal in maize-cotton seed meal based diets. A total of 144 day old Aback 80 strain broiler chicks were used. Triplicate groups of 12 birds were randomly allotted on 4 diets containing 0, 1, 1.5 and 2% RRP which contributed 0,350,525 and 700 mg/kg Fluorine (F) levels in the diets. Results showed that when 1.5% RRP replaced equal amount of bone meal, weight *gain and growth rate were not significantly different (P>0.05) from birds fed 3% bone meal control diet (i.e. 0% RRP). Inclusion of 1% RRP (i.e. 350mg/kg F) in the diet supported the highest growth rate during 0-4 week period, but it was not significantly different from birds fed the control or 1.5% RRP diets... RRP at 2% (700mglkg F) caused significantly (P<0.05) poorer performance than the other treatment groups. Feed intake was not significantly affected by dietary treatments. It was concluded from this study that 1.5% RRP appear to represent the upper limit that could substitute equal amount of bone meal for adequate growth. This represented 50% replacement of bone meal by RRP in broiler diets. Broiler chicks appears to tolerate 525mglkg F* without detrimental effect on performance. However, 1% RRP (350mglkg F) seemed to have stimulatory effect on growth and promoted optimum feed efficiency up to 4 weeks of age.